CITRA TOYOTA AVANZA MELALUI TANDA VERBAL DAN VISUAL IKLAN PRODUK TOYOTA TAHUN 2018: KAJIAN SEMIOTIK - Mohammad Fahmi Heryanda; Dian Indira; Nani Darmayanti (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2018)
Toyota Avanza is one of the most enthused car brands in Indonesian society. Advertisement is one of available tools used by producer companies in promoting their products, either by verbal means or nonverbal means, just like Toyota Avanza advertisements in 2018. The present research is a semiotic study that analyzes the relation between signifier and signified in constructing meaning. The present research uses qualitative research method by describing, interpreting, and explaining both signifier and signified of verbal as well as visual signs based on Barthes’ (1957) semiotic theory. The particular method is applied to construe the denotative and connotative meaning of Toyota Avanza advertisements in 2018 and eventually to identify the image of the advertised product. The technique of data collecting used in the present research is observation technique. The aims of the research are to unfold the meaning behind the verbal and visual signs present in the advertisements and to reveal the image and the identity of the advertisements products. The results show that the advertisements contain more informative verbal signs and thus the connotative meanings of such signs determine how the product image is perceived by the consumers.